Pengelolaan Konflik Di SMK Negeri 1 Purwodadi - NURCAHYANINGSIH, EMI (2016)
This research has three aims. (1) To describe the management of conflict sources in SMK Negeri 1 Purwodadi. (2) To describe the types of management conflict in SMK Negeri 1 Purwodadi. (3) To describe the handling of management conflict in SMK Negeri 1 Purwodadi. The research was qualitative research design using an ethnographic approach. Method of data collection was done by interview, observation and documents. The analysis method was interaktif analysis. The results of the research there are three result. (1) Management of conflict sources in SMK Negeri 1 Purwodadi can not be separated from the roles of principal and vice-principals of the school as a mediator and also as a motor of effective management conflict and give positive impact to the progress of the school. (2) Types of management conflict in SMK Negeri 1 Purwodadi include all kinds of conflict that consisted the conflict of students, teachers and also employee. Basically the conflict that happened in SMK Negeri 1 Purwodadi is the conflict among the teachers, teachers with employee and the conflict with students minimal. (3) The handling of management conflict in SMK Negeri 1 Purwodadi, to solve the conflicts have carried out eight strategies that the principals 1) uses SWOT management strategy which is a strategic planning method used to evaluate the strengths, weaknesses, opportunities and threats as a scope of learning in school; 2) the value planting TOP (Tangguh Optimis Pemberani); 3) mediatioan; 4) invite quest teachers; 5) the assembly instruction; 6) the reorganization of the structure; 7) in house training (IHT); and 8) the preparation of the job description.